2019
DOI: 10.1029/2019jc015331
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Spatial Scales of Correlation in Marine Phytoplankton Communities

Abstract: Ocean circulation shapes marine phytoplankton communities by setting environmental conditions and dispersing organisms. In addition, processes acting on the water column (e.g., heat fluxes and mixing) affect the community structure by modulating environmental variables that determine in situ growth and loss rates. Understanding the scales over which phytoplankton communities vary in time and space is key to elucidate the relative contributions of local processes and ocean circulation on phytoplankton distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 61 publications
2
41
0
Order By: Relevance
“…For this study, the 20-year mean of these outputs was used as the input for the eco-provinces. Distribution of Chl, plankton biomass, and nutrient concentrations, as well as distributions of functional groups compare well with satellite and in situ observations [see (2,44), note S1, and figs. S1 to S3].…”
Section: Model Frameworksupporting
confidence: 65%
See 1 more Smart Citation
“…For this study, the 20-year mean of these outputs was used as the input for the eco-provinces. Distribution of Chl, plankton biomass, and nutrient concentrations, as well as distributions of functional groups compare well with satellite and in situ observations [see (2,44), note S1, and figs. S1 to S3].…”
Section: Model Frameworksupporting
confidence: 65%
“…Parameters influencing phytoplankton growth, grazing, and sinking are related to size, with specific differences between the six phytoplankton functional groups (32). Results from this 51 plankton component of the model have been used in several recent studies (42)(43)(44), though in a different physical framework.…”
Section: Model Frameworkmentioning
confidence: 99%
“…CC BY 4.0 License. between different size classes of those (Kuhn et al, 2019;Trudnowska et al, 2016), which may explain why we observed different distribution patterns of various size fractions (e.g. the Pico fraction was mostly confined to the upper few meters while having wide horizontal distribution, whereas the Micro and Small fraction patches extended frequently over wide vertical ranges, but had much smaller horizontal range).…”
Section: Patch Structurementioning
confidence: 78%
“…To make matters more complicated, the dominating mechanisms vary depending on the scale, location or time of the year (Martin, 2003), e.g., the relative importance of the biotic processes increases inversely with scale (Pinel-Alloul, 1995), because the physical processes act naturally at different timescales than plankton growth and activity (Mahadevan, 2016). Also the local processes and ocean circulation operate on very different scales, making it extremely difficult to elucidate their relative contributions on particles and plankton distributions (Kuhn et al, 2019). In the case of the patches analysed in this study, the local environmental variables were the most crucial in the case of the fjord, where smaller spatial scale was investigated (Isfjorden), whereas the spatial effect was privileged when the larger distance and thus wider spectrum of environments was considered (Kongsfjorden).…”
Section: The Interplay Between Local and Oceanic Processesmentioning
confidence: 99%
“…Yet, phytoplankton exudates and other dissolved organic matter exist as complex mixtures of compounds which differ in their abundance, diffusivity and propensity to elicit chemotaxis (Davis and Benner, 2007;Duursma and Dawson, 2011). Emerging analytical methods of characterizing chemical microenvironments, exudation rates and nutrient exchanges (Wessel et al, 2013) will further inform models for microbial motion (Keller and Segel, 1970;Jackson, 1987;Bray et al, 2007;Desai et al, 2019) through to ocean-scale dynamics of microbial populations (Barton et al, 2010;Worden et al, 2015;Kuhn et al, 2019).…”
Section: Priorities For Future Researchmentioning
confidence: 99%